Research on Gear Profile Modification based on Thermal-fluid-solid Coupling - Yi Yangfan Lan Huiqing Yu Sitai (Jixie chuandong)
In order to study the influence of profile modification on the internal flow field，temperature field and stress field of the gearbox system，the gear with or without modification are accurately modeled by Pro/E. The fluid field of gearbox system is calculated by overset grid method，and the steady calculation result is transmitted to the boundary of the gear to solve the temperature field and the stress field，i.e. thermal-fluid-solid coupling numerical simulation is used to study the gearbox oil bath lubrication. The lubrication volume fraction of the end part of gear pair，internal pressure variance of the gearbox，temperature and stress distribution of the gear solid body are compared and analyzed under different modification conditions. The results show that when b=1（i.e. straight-line modification），the temperature field and stress field of the gear are not improved much，and the modification effect is not evident. Then, when b=2, and when b=1.22，the modification show the best effect. No matter what kind of modification curve is used，the stress concentration of the gear root could be significantly improved.